CONTRIBUTION TO THE FLORA OF THE SOUTH AEGEAN VOLCANIC ARC: KIMOLOS ISLAND (KIKLADES, GREECE). (13th June 2014) - Kougioumoutzis, K.; Tiniakou, A.; Georgiou, O.; Georgiadis, T.
Abstract : The island of Kimolos, located in the western Kiklades in Greece, constitutes together with Milos, Polyaegos, Anafi and the Santorini island group the central part of the South Aegean Volcanic Arc. The flora of Kimolos consists of 443 taxa, 70 of which are under a statute of protection, 30 are Greek endemics and 225 are reported here for the first time. We show that Kimolos has the highest percentage of Greek endemics in the South Aegean Volcanic Arc. The known distribution of the endemics Sedum eriocarpum subsp. eriocarpum and Anthemis rigida subsp. liguliflora is expanded, being reported for the first time for the phytogeographical region of the Kiklades. The floristic cross-correlation between Kimolos and other parts of the South Aegean Volcanic Arc by means of Sørensen's index revealed that its phytogeographical affinities are somewhat stronger to Anafi than to neighbouring Milos.